The New Rules for Crisis Management - Hunter, Mark; Van Wassenhove, Luk; Besiou, Maria; Haanaes, Knut (MIT Sloan Management Review, 2016)
In today's world, the traditional news media do not always control how crises unfold. Executives may face stakeholder communities that control their own sources of information and their own media and have their own ideas about how companies should resolve crises. These stakeholder groups wield considerable power to influence other stakeholders, organizations, and the public, and executives who ignore them do so at their own peril. On more than one occasion in the past decade, entire divisions of multinational companies were sold off to competitors after stakeholders criticized those businesses through their proprietary media. Thus, companies need to know how stakeholders gained this power, how they use it, and what to do about them. Stakeholders have become both increasingly active and more diverse. Their numbers now include social activists, expert financial analysts, and liability lawyers in addition to employees, customers, and business partners. To spread their messages and encourage people to connect and interact with one another, stakeholders are now deploying a variety of channels, including websites, user forums, e-newsletters, videos, and social media platforms. By following the connections among their various media, the authors have observed the ways these stakeholder groups find and influence one another, building their communities and aligning with others who share similar objectives. Individually, many of these stakeholders may be powerless, but together, they can have a huge impact on how a crisis evolves. Moreover, by creating their own media, these stakeholders can bypass the "gatekeepers" of traditional media: the editors and journalists who in the past decided what news was fit to publish. To understand the role of stakeholder-controlled media in controlling how a corporate crisis unfolds, the authors investigated numerous events in which stakeholders seemed to dictate how the action played out. In those crises, they found that the stakeholders were able to leverage three key assets: frontline information, their own news channels, and the ability to determine when and how a crisis ends. The authors offer recommendations about how companies should respond to stakeholder concerns during a crisis.